2021
DOI: 10.3390/plants10061167
|View full text |Cite
|
Sign up to set email alerts
|

Utilization of a Wheat50K SNP Microarray-Derived High-Density Genetic Map for QTL Mapping of Plant Height and Grain Traits in Wheat

Abstract: Plant height is significantly correlated with grain traits, which is a component of wheat yield. The purpose of this study is to investigate the main quantitative trait loci (QTLs) that control plant height and grain-related traits in multiple environments. In this study, we constructed a high-density genetic linkage map using the Wheat50K SNP Array to map QTLs for these traits in 198 recombinant inbred lines (RILs). The two ends of the chromosome were identified as recombination-rich areas in all chromosomes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(6 citation statements)
references
References 75 publications
(98 reference statements)
1
5
0
Order By: Relevance
“…Similarly, four MTAs were identified on 3D, 2D, 3A, and 2B for TKW. MTAs for TKW on the same chromosomes in different mapping populations were also identified in earlier reports on 1B [ 27 ], 2B [ 28 , 91 ], 2D [ 25 , 80 , 91 , 92 , 93 ], 3A [ 88 , 93 , 94 , 95 ] at different chromosomal locations. Cabral et al [ 27 ] identified a QTL, i.e., QGwt.crc-2B-2 , on the 2B chromosome, located at a confidence interval of 92.9–96.0 cM, which was similar to the MTA ( AX-95194336 ) detected in the current study on the same chromosome at 96.2 Mb.…”
Section: Discussionsupporting
confidence: 77%
“…Similarly, four MTAs were identified on 3D, 2D, 3A, and 2B for TKW. MTAs for TKW on the same chromosomes in different mapping populations were also identified in earlier reports on 1B [ 27 ], 2B [ 28 , 91 ], 2D [ 25 , 80 , 91 , 92 , 93 ], 3A [ 88 , 93 , 94 , 95 ] at different chromosomal locations. Cabral et al [ 27 ] identified a QTL, i.e., QGwt.crc-2B-2 , on the 2B chromosome, located at a confidence interval of 92.9–96.0 cM, which was similar to the MTA ( AX-95194336 ) detected in the current study on the same chromosome at 96.2 Mb.…”
Section: Discussionsupporting
confidence: 77%
“…The highest number of 12 QTLs were identified for PH on the 1B, 2B, 3A, 3B, 3D, 4A, 5A, 5D, 7B, and 7D chromosomes. Plant height is one of the important yield component traits in wheat, and therefore many QTLs were also identified in previous reports on chromosomes 1B [ 10 , 19 , 37 , 40 , 51 ], 2B [ 10 , 40 , 45 , 51 , 53 ], 3A [ 26 , 54 ], 3B [ 10 , 19 , 22 , 40 ], 4A [ 26 , 45 , 52 , 53 ], 5A [ 19 , 26 , 45 , 51 , 53 , 55 , 56 ], and 7B [ 10 ], at different positions. In addition, Alemu et al [ 52 ] identified a QTL on the 4A chromosome at 41cM, which was similar to that of QPH-4A and mapped at 41cM, explaining a 4.58% phenotypic variation.…”
Section: Discussionmentioning
confidence: 70%
“…Eight QTLs were identified for TKW on the 3A, 4A, 5A, 5B, 6A, and 7D chromosomes. Previous reports also identified some QTLs on the same chromosomes: 3A [ 10 , 19 , 24 , 50 , 56 ], 4A [ 19 , 31 , 46 , 50 ], 5A [ 23 , 29 , 40 , 57 ], 5B [ 20 , 29 , 40 , 45 , 52 , 53 , 54 , 57 ], 6A [ 23 , 29 , 31 , 37 , 46 , 48 , 50 , 52 , 53 , 55 , 56 , 57 ], and 7D [ 29 , 31 , 40 , 50 ], at different positions. In addition, three previous reports, i.e., Gahlaut et al [ 19 ], Edae et al [ 46 ], and Ramya et al [ 27 ] identified a QTL at 73 cM, 72.4 cM, and 70 cM, respectively, on the 5B chromosome, which was similar to the QTL ( QTKW-5B ) identified in the present study at 70.5–73.5 cM, on the same chromosome.…”
Section: Discussionmentioning
confidence: 91%
“…Genetic map or genetic linkage map refers to the relative location and genetic distance of a gene or molecular marker on a chromosome, which is different from the real distance in a physical map ( Meng et al, 2015 ; Yagi et al, 2017 ; Lv et al, 2021 ). Genetic distance in a genetic map is calculated from the recombination rate of genes or markers.…”
Section: Discussionmentioning
confidence: 99%